2021
DOI: 10.3390/rs13224546
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Wide-Area Norwegian Spring-Spawning Herring Population Density with Ocean Acoustic Waveguide Remote Sensing (OAWRS)

Abstract: Norwegian spring-spawning herring are a critical economic resource for multiple nations in the North Atlantic and a keystone species of the Nordic Seas ecosystem. Given the wide areas that the herring occupy, it is difficult to accurately measure the population size and spatial distribution. Ocean Acoustic Waveguide Remote Sensing (OAWRS) was used to instantaneously measure the areal population density of Norwegian herring over more than one thousand square kilometers in spawning grounds near Ålesund, Norway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The data presented here are from the Gulf of Maine 2006 OAWRS Experiment (Figure 1) conducted on the western flank of Georges Bank area from 19 September to 6 October 2006, in conjunction with the U.S. National Marine Fisheries Service Annual Atlantic Herring Acoustic Survey [4,5,14]. In this experiment, spatial and temporal population density distributions, group behavior and physical scattering characteristics of Atlantic Herring (Clupea harengus) were quantified during their annual spawning period in their primary spawning ground in the Gulf of Maine [6][7][8]10,12,13,[16][17][18][19]28].…”
Section: Oawrs Gulf Of Maine 2006 Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data presented here are from the Gulf of Maine 2006 OAWRS Experiment (Figure 1) conducted on the western flank of Georges Bank area from 19 September to 6 October 2006, in conjunction with the U.S. National Marine Fisheries Service Annual Atlantic Herring Acoustic Survey [4,5,14]. In this experiment, spatial and temporal population density distributions, group behavior and physical scattering characteristics of Atlantic Herring (Clupea harengus) were quantified during their annual spawning period in their primary spawning ground in the Gulf of Maine [6][7][8]10,12,13,[16][17][18][19]28].…”
Section: Oawrs Gulf Of Maine 2006 Experimentsmentioning
confidence: 99%
“…The OAWRS technology has been shown to enable instantaneous population density quantification and continuous monitoring of fish populations over thousands of square kilometers, with space-time sampling rates tens of thousands to millions of times higher than line transect methods by employing the natural capacity of the oceans for long-range sound channeling at lower frequencies [3,4,6]. Fish populations and behavior have been studied with OAWRS over wide areas in the Mid-Atlantic Bite [3], the Gulf of Maine [7] and the Nordic Seas [8][9][10][11]. To summarize some key results, the instantaneous horizontal structures and volatile short-term behavior of very large fish shoals, containing tens to hundreds of millions of fish and stretching for many kilometers, have been revealed by OAWRS, including the presence of population density waves within the shoals that exceed fish swimming speeds [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…caused by population growth or develop new technologies for energy surveys (for mineral exploration, etc.) to reduce costs and improve the efficiency of energy exploration (Duane et al, 2021;Chen et al, 2022;Wu et al, 2022). Gonzalez and Gonzalez, 2016;Hu et al, 2019), which means that it takes time from publication to citation (Campanario, 2011;Chi, 2016).…”
Section: Category I Z(i)mentioning
confidence: 99%
“…At the same time, low visibility of underwater observation makes underwater signal sensing mainly rely on hydrophones, and acoustic waves have become the main medium of underwater observation. Although lots of studies have shown the great potential of acoustic waves for underwater observation, they are limited by complex underwater environments, and obtained detection results include target signals and substantial background noises [3], [4]. At the same time, generally acquired oceanic acoustic observation signals are nonstationary nonlinear signals, and the conventional frequency domain analysis method and second-order domain method cannot accurately distinguish the target signal from background noise.…”
Section: Introductionmentioning
confidence: 99%